After war (Medicine Anthropology Theory, 2016)
In the United States – as in other places in the ambit of biomedicine – the efforts exerted on and by injured soldiers’ bodies in the aftermath of war are generally understood under the familiar medical rubric of ‘rehabilitation’. This reflection troubles that term by moving away from the medical logic of rehabilitation and its telos of injury and healing, and the logics that see injured soldiers as promising bodies. Instead, the think piece explores a wider range of practices of attention to injured soldiers’ bodies that emerge ethnographically, and traces embodied forms of being made within unsteady temporalities of life, health, and death after war, forms that call the temporality of rehabilitation into question and highlight care’s collateral affects. I reflect on the phenomenon of heterotopic ossification – bone growth at the site of injury that is a sign of healing that is also itself a form of injury – to think through the confounding analytical, ethical, political, and corporeal implications of such a space.